CTD bottle data from RV POLARSTERN cruise PS137 at Lucky B site - Walter, Maren; Mette, Jonathan (PANGAEA, 2025)
This dataset contains aggregated CTD (conductivity, temperature, depth probe) data corresponding to bottle closures for water sampling for stations conducted during the cruise PS137. Additionally it contains the corresponding helium isotope ratio measured in the lab post-cruise and navigational data from the ships positioning system. The two stations were executed to detect possible hydrothermal plumes at the Lucky B site where hydrothermal activity was suspected at approximately 81° latitude and -3° longitude. The data was measured with a CTD rosette system and processed to correct sensor uncertainties and remove outliers. For every parameter the mean, standard deviation, minimum and maximum are given which are associated with the time interval of closing one sample bottle.
Keywords: Arctic Ocean; CTD; hydrothermal activity; Lucky B